2020
DOI: 10.1186/s12886-020-01402-3
|View full text |Cite
|
Sign up to set email alerts
|

Case report of conjunctival sac fistula after cosmetic lateral canthoplasty

Abstract: Background: To report a case of conjunctival sac fistula after cosmetic lateral canthoplasty which is rare. Case presentation: A young women who underwent bilateral canthoplasty appeared with lacrimation of the right eye. We found there was a skin fistula with transparent tears at 2 mm lateral to the right canthus ligament and the liquid containing fluorescein was seen to overflow at the fistula after using fluorescein sodium eye drops. The number 7 lacrimal duct probe was visible under the temporal conjunctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In a retrospective medical record review, four patients reported tearing from a lacrimal ductile fistula following lateral canthoplasty to lengthen a horizontal palpebral fissure [28]. Furthermore, it has been reported that during surgery, accidental suturing of conjunctival tissue with skin tissue resulted in the proliferation of conjunctival epithelial cells, leading to the formation of a fistula connecting the skin and conjunctival sac [29].…”
Section: Mz Cat Eye Liftmentioning
confidence: 99%
“…In a retrospective medical record review, four patients reported tearing from a lacrimal ductile fistula following lateral canthoplasty to lengthen a horizontal palpebral fissure [28]. Furthermore, it has been reported that during surgery, accidental suturing of conjunctival tissue with skin tissue resulted in the proliferation of conjunctival epithelial cells, leading to the formation of a fistula connecting the skin and conjunctival sac [29].…”
Section: Mz Cat Eye Liftmentioning
confidence: 99%
“…In a retrospective medical record review, four patients reported tearing from a lacrimal ductile fistula following lateral canthoplasty to lengthen a horizontal palpebral fissure [28]. Furthermore, it has been reported that during surgery, accidental suturing of conjunctival tissue with skin tissue resulted in the proliferation of conjunctival epithelial cells, leading to the formation of a fistula connecting the skin and conjunctival sac [29].…”
Section: Mz Cat Eye Liftmentioning
confidence: 99%
“…However, improper operations during the surgery sever the lateral canthus and lead to various complications 2 (Fig. 1A), including canthal webbing, rounding canthus, margin defect, remnant raw surface, mucosal exposure, sclera show, ectropion, lacrimal ductal fistula, 4 and conjunctival sac fistula 5 …”
mentioning
confidence: 99%
“…1A), including canthal webbing, rounding canthus, margin defect, remnant raw surface, mucosal exposure, sclera show, ectropion, lacrimal ductal fistula, 4 and conjunctival sac fistula. 5 As the lateral canthus is anatomically where the upper and lower lids meet laterally, 6 symmetric, normally shaped, and positioned lateral canthus are the cornerstones of youthful periorbital appearance. 7 Revision of complications is of paramount importance to ensure appropriate canthal contour and eyelid function.…”
mentioning
confidence: 99%